Gambus Johor sustainability: issues and challenges / Siti Nur Shahirah Hussin and Tazul Izan Tajuddin - Hussin, Siti Nur Shahirah; Tajuddin, Tazul Izan (Universiti Teknologi MARA, Perak, 2022)
Identifying the issues and challenges faced by different parties, departments, and agencies throughout the process can help find solutions to solve these issues and challenges. Then, achieving the article's goal of sustaining the Gambus Johor musical instruments and music for future generations. The purpose of this article is to list out and discuss the issues and challenges of sustaining the Gambus Johor musical instrument and music faced by the radio stations, television stations, the government especially the Ministry of Tourism, Arts, and Culture, school authorities, and Ministry of Communications and Multimedia in Malaysia.